دافعية الإنجاز وعلاقتها بالثقة بالنفس لدى لاعبي كرة القدم حسب مراكز اللعب -دراسة ميدانية على بعض أندية الجهوي الأول لأقل من 18 سنة بولاية باتنة- - بهلولي, صدام; بن يحي, أسامة (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة إلى معرفة العلاقة بين دافعية الإنجاز والثقة بالنفس لدى لاعبي كرة القدم، حيث قمنا بإستخدام المنهج الوصفي، و قد تم الإعتماد على كل من مقياس دافعية الإنجاز لـ: جو ولس المتكون من 40 عبارة موزعة على 03 أبعاد، ومقياس سيدني شروجر الذي قام الدكتورعادل عبد الله محمد بترجمته وتعريبه، وقمت بصفتي كباحث بعرضه على المحكمين وحذف بعض العبارات بما يتناسب مع عينة بحثي، حيث يتكون المقياس في شكله الأصلي من 54 عبارة، تم إستبعاد ست منها عند قيام المترجم المقنن بإجراء التحليل العاملي ليصبح عدد العبارات 48، وبعد عرضه على المحكمين أصبح يتكون من 38 عبارة مسقمة على بعدين، كما استعملنا مجموعة من الأساليب الإحصائية معامل الإرتباط بيرسون،إختبار التباين الأحادي،المتوسط الحسابي،والإنحراف العياري، وبعد تطبيق الدراسة توصلنا إلى أن هناك علاقة بين دافعية الإنجاز والثقة بالنفس لدى لاعبي كرة القدم. This study aims to discover the relationship between achievement motivation and self-confidence for football players according to their playing position.Weused the descriptive approach, so we relied on achievement motivation scale of Jo Walsh, which consists of 40 expressions distributed into 03 aspects and Sidney Shroger’s Scale which was translated into Arabic by Adal Abd-Allah Mohammed. As a researcher I have presented it to the judges then omitted some expressions to suit my work; which consists in its original form 54 expressions,6 of them were excluded through using the logical analysis so the number of the expressions became 48; afterexposing it to the judges it becomes 38 divided on two dimensions; also we used a set of statistical methods: Person’s correlation, the ANOVA test, arithmetic mean and standard deviation; after applying the study we deduce that there is a relationship between achievement motivation and self-confidence.
Achievement motivation and its relationship to self-confidence among soccer players, according to the playing centers( a field study on some of the first regional clubs for less than 18 years in the wilaya of Batna)
مقال
Keywords: دافعية الإنجاز، الثقة بالنفس، لاعبي كرة القدم